Global‐scale seasonally resolved black carbon vertical profiles over the Pacific. Issue 20 (23rd October 2013) - Schwarz, J. P.; Samset, B. H.; Perring, A. E.; Spackman, J. R.; Gao, R. S.; Stier, P.; Schulz, M.; Moore, F. L.; Ray, Eric A.; Fahey, D. W.
Abstract [1] Black carbon (BC) aerosol loadings were measured during the High‐performance Instrumented Airborne Platform for Environmental Research Pole‐to‐Pole Observations (HIPPO) campaign above the remote Pacific from 85°N to 67°S. Over 700 vertical profiles extending from near the surface to max 14 km altitude were obtained with a single‐particle soot photometer between early 2009 and mid‐2011. The data provides a climatology of BC in the remote regions that reveals gradients of BC concentration reflecting global‐scale transport and removal of pollution. BC is identified as a sensitive tracer of extratropical mixing into the lower tropical tropopause layer and trends toward surprisingly uniform loadings in the lower stratosphere of 1 ng/kg. The climatology is compared to predictions from the AeroCom global model intercomparison initiative. The AeroCom model suite overestimates loads in the upper troposphere/lower stratosphere ( 10×) more severely than at lower altitudes ( 3×), with bias roughly independent of season or geographic location; these results indicate that it overestimates BC lifetime.